Acculturation of Western and Local Occult Symbols in the Film Pengabdi Satan 2: Communion (Semiotic Analysis of Roland Barthes) - Fauzi Taufik Rabani; Twin Agus Pramonojati; Rizca Haqqu (JURNAL DIGITAL MEDIA, CULTURE, AND HUMANITIES, 2025)
This study aims to analyze the form and meaning of the acculturation of Western and local occult symbols in the Indonesian horror film Pengabdi Setan 2: Communion. As national cinema evolves, the horror genre has transformed from merely exploiting local myths to complex narratives integrating global occult elements. This research employs a qualitative method with Roland Barthes semiotic approach to dissect the layers of denotative, connotative, and mythical meanings in the film's scenes, characters, and properties. The analysis results indicate strong symbolic hybridization, where Western occult artifacts such as the Ouroboros and Satanic Cross are recontextualized alongside local entities like pocong and pesugihan practices. Main findings reveal that these symbols are not merely visual elements but function to build a new myth about the universality of terror. The talisman symbol shifts function into a communication medium, while local ghost figures are placed within an international cult ritual structure. In conclusion, this film represents a cultural acculturation that successfully creates a relevant horror atmosphere, asserting that occult practices in modern cinema serve as a cultural communication bridge binding its adherents in an endless cycle of sacrifice, while reflecting the adaptive dynamics of Indonesian societal beliefs toward external influences.